Institutional environment of the Brazilian tilapia production: an analysis from multidimensional indexes - Ribeiro, Vinícius Souza; Pedroza Filho, Manoel Xavier (Revista de Economia e Sociologia Rural, 2025)
Abstract The Global Value Chains literature recognizes the importance of institutions for both countries and firms, although the subject is under-researched in empirical studies in the field. In this context, this research aims to discuss the institutional environment of tilapia production in Brazil. The institutional environment indexes were estimated using fuzzy modeling from three perspectives (Economic, Social, and Local). The data was collected in a region with a high capacity to lead value chain internationalization. The results indicate that spatial specialization may be a factor leading to a higher offer of credit to production units. However, access to this credit for units located in the production zone may be more difficult due to the requirements of the environmental and operational laws in that area. In this context, we argue that the main bottlenecks of the chain (credit and legal compliance) may create a harmful feedback effect, especially for small farmers. Additionally, we point out the necessity of more efficient communication in terms of the socioeconomic and environmental benefits of the chain. Finally, we highlight the importance of strengthening the institutional framework and social capital for small producers as crucial factors to overcome bottlenecks and ensure sustainability in the Brazilian tilapia value chain. Resumo A literatura sobre Cadeias Globais de Valor reconhece a importância das instituições tanto para os países quanto para as empresas, embora o assunto seja pouco estudado em estudos empíricos no campo de pesquisa. Neste contexto, este estudo visa discutir o ambiente institucional da produção de tilápia no Brasil. Os índices do ambiente institucional foram estimados utilizando modelos fuzzy a partir de três perspectivas (Econômica, Social e Local). Os dados foram coletados em uma região brasileira com alta capacidade para liderar a internacionalização da cadeia de valor. Os resultados indicam que a especialização espacial pode ser um fator que leva a uma maior oferta de crédito às unidades de produção. Entretanto, o acesso a este crédito para unidades localizadas na zona de produção pode ser mais difícil devido às exigências legais ambientais e operacionais naquela área. Neste contexto, argumentamos que os principais gargalos da cadeia (crédito e conformidade legal) podem criar um efeito de feedback prejudicial, especialmente para os pequenos agricultores. Além disso, apontamos a necessidade de uma comunicação mais eficiente em termos dos benefícios socioeconômicos e ambientais da cadeia. Finalmente, destacamos a importância de fortalecer a estrutura institucional e o capital social dos pequenos produtores como fatores cruciais para superar os gargalos e garantir a sustentabilidade na cadeia nacional de valor da tilápia.